2011
DOI: 10.4061/2011/721613
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of MLC601 in Iranian Patients after Stroke: A Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Objective. To investigate the safety and efficacy of MLC601 (NeuroAid) as a traditional Chinese medicine on motor recovery after ischemic stroke. Methods. This study was a double-blind, placebo-controlled clinical trial on 150 patients with a recent (less than 3 month) ischemic stroke. All patients were given either MLC601 (100 patients) or placebo (50 patients), 4 capsules 3 times a day, as an add-on to standard stroke treatment for 3 months. Results. Sex, age, elapsed time from stroke onset, and risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…This is consistent with previously published studies on MLC601, which detected improved functional outcomes and motor recovery among mainly nonacute ischemic stroke patients. 11,12,14 These findings support the possible neurorestorative effects of MLC601 and would be topics of interest for further nonclinical and clinical investigations.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This is consistent with previously published studies on MLC601, which detected improved functional outcomes and motor recovery among mainly nonacute ischemic stroke patients. 11,12,14 These findings support the possible neurorestorative effects of MLC601 and would be topics of interest for further nonclinical and clinical investigations.…”
Section: Discussionsupporting
confidence: 66%
“…Because previous studies on MLC601 suggested a benefit in nonacute ischemic stroke patients, [11][12][13][14][15][16][17] the time window of 72 hours was chosen for this study in an attempt to test both the neuroprotective and neurorestorative properties of MLC601.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study was identified through personal contact of the author (C.C.). In total, 5 studies were short-listed for full text evaluation [7,14,15,16,17]. Of these, 1 was the previous systematic review of 2 unpublished Chinese trials.…”
Section: Resultsmentioning
confidence: 99%